Development of Literation based Thematic Integrated Teaching Materials using Microsoft Sway for Class V Students of Elementary Schools - Fadhli Fadhli; Zelhendri Zen; Yanti Fitria (International Journal of Educational Dynamics, 2021)
The integrated thematic textbook developed by the government and becoming a learning resource for elementary students already has the characteristics of literacy learning. However, using them for studying online is less effective. Therefore it is necessary to develop a teaching material that uses an online program/media which can be a reading source as well as a place to do exercises. This research is a development research using the Borg and Galls design. The evaluation method used refers to a formative evaluation design consisting of expert reviews and small group evaluations. The validity data were collected through the validation of teaching materials by 5 experts and analyzed using quantitative descriptive techniques. Practicality data were collected through observing the implementation of learning, and filling out questionnaires by teachers and students. The collected data from observations and questionnaires were analyzed descriptively and quantitatively. The results showed that the average expert and practitioner assessment of the content validity was 3.12 with the valid category and the construct validity 3.15 with the valid category. The average practicality assessment by students was 3.24 and by the teacher 3.25. This shows that the teaching materials developed are very practical. It can be concluded that literacy-based integrated thematic teaching materials using Microsoft Sway for grade V elementary school students developed are valid and very practical.